FEATURES OF THE HERO’S IDENTIFICATION IN V. PELEVIN’S NOVEL IPHUCK 10 (Eureka Journal of Language, Culture & Social Change, 2026)
The article examines the image of the devil in F. M. Dostoevsky’s novel The Brothers Karamazov as one of the most philosophically profound figures in Russian literature. Special attention is given to the chapter “The Devil. Ivan Fyodorovich’s Nightmare,” in which the devil appears not as a supernatural being but as the personified inner voice of Ivan Karamazov. The analysis focuses on the devil’s outward appearance, manner of behavior, and ideological function within the text. It is shown that the devil acts as the philosophical and moral double of the protagonist, logically carrying his ideas to the point of absurdity. The article also reveals the connection between Ivan Karamazov’s worldview and the philosophies of Kant and Nietzsche, and interprets Ivan as a model of modern human consciousness, possessing absolute moral sensitivity while experiencing a crisis of meaning.
Keywords: F. M. Dostoevsky, Ivan Karamazov, image of the devil, philosophical double, nihilism, suffering, moral maximalism, Kant, Nietzsche.